Virtual Reality Berbasis Video 360O Sebagai Alternatif Penyampaian Informasi Pelayanan Rumah Sakit - Prayoga Pribadi; Triana Nur Cahyani; Retno Waluyo; Dhanar Intan Surya Saputra; Sitaresmi Wahyu Handani (Ikatan Ahli Informatika Indonesia (IAII), 2019)
The hospital is a health service institution that provides full range of personal health services providing inpatient, outpatient and emergency care services. Most hospitals, outpatient services are one of the most important services because the number of patients is more significant than inpatient services, requiring more attention in providing services and delivering information to patients. Submission of information on outpatient services, doctor's schedules, types of payments and several other services at the Hospital were developed to provide innovation, one of them using virtual reality technology as an alternative media so that the delivered message will be easily understood by patients and society. This research uses MDLC (Multimedia Development Life Cycle) development method. The results of this study is 360-based virtual reality video as an alternative media to deliver information that is expected to help the public in obtaining information about outpatient services in the Hospital.